高效和大功率密度船用喷水推进泵水力模型的设计方法 (2017)
本发明公开了高效和大功率密度船用喷水推进泵水力模型的设计方法，包括如下步骤：喷水推进泵水力参数的选型设计，确定二维轴面投影几何，采用参数化三元逆向设计方法获得叶轮和导叶的三维几何形状，周向旋转得到收缩喷口的三维几何形状，将叶轮、导叶和收缩喷口的三维几何形状组合得到喷水推进泵水力模型。本发明具有设计周期短、设计质量高的显著特点，可快速、可靠设计出同时具有高效、紧凑、大功率密度特征的喷水推进泵水力模型。通过参数化三元逆向设计叶轮和导叶叶片几何，解决了高速船舶喷水推进泵研发过程中在尽量保持紧凑的条件下同时提高效率、抑制空化和增加功率密度的难题。 The invention discloses a method for designing a water-spraying boost pump hydraulic model for an efficient and large-power-density ship. The method comprises the following steps that type selection design of water-spraying boost pump hydraulic parameters is conducted, two-dimensional axial face projective geometry is determined, three-dimensional geometrical shapes of an impeller and guide blades are obtained according to a parameterized ternary reversal design method, a three-dimensional geometrical shape of a shrinkage nozzle is obtained through circumferential rotation, the three-dimensional geometrical shapes of the impeller, the guide blades and the shrinkage nozzle are combined to obtain the water-spraying boost pump hydraulic model.